Functional and Structural Consequences of Single-Nucleotide Polymorphisms in the NPM1 Gene Associated with Acute Myeloid Leukemia: Insights from a Comprehensive Bioinformatics Approach - Tamosree Sikder; Mijan Mia; Nazmul Rahman Chowdhury; Md. Emdadul Islam (Journal of Bio-X Research)
NPM1 is a protein-coding gene that encodes the nucleophosmin 1 (NPM1) protein. The NPM1 protein exhibits dynamic shuttling between the nucleus and cytoplasm and is involved in various cellular processes, such as centrosome duplication, protein chaperoning, and DNA repair. Mutations of the NPM1 gene are associated with human acute myeloid leukemia (AML). AML is a complex hematopoietic cell disorder characterized by excessive proliferation of hematopoietic cells of the myeloid lineage in the bone marrow. This study aimed to predict highly damaging missense single-nucleotide polymorphism (SNPs) in the human NPM1 gene that may be associated with AML. In this investigation, we employed a range of in silico tools to analyze the functional and structural consequences of missense SNPs in the human NPM1 gene. The missense SNPs of the NPM1 gene were retrieved from the Ensembl database. We evaluated the functional and structural impacts of missense SNPs using bioinformatics tools, specifically SIFT, PROVEAN, PolyPhen-2, I-Mutant 3.0, MUpro, and MutPred2. The secondary structure was predicted with PSIPRED. The 3-dimensional structure of the NPM1 protein was obtained from AlphaFold, visualization along with mutant models was generated using PyMOL, and all information about physiological properties was taken from the HOPE project. The protein–protein interactions of the NPM1 protein were investigated using STRING. In silico analysis revealed 8 missense mutations (K54N, I59T, L79S, P152A, K193R, K193N, A283G, and I284F) in the human NPM1 gene. These mutations lead to structural alterations in the protein, which disrupt its normal function and may contribute to the development of AML in humans.